Effectiveness of quadrivalent influenza vaccine in pregnant women and infants, 2018–2019. Issue 29 (15th June 2020) - Maltezou, Helena C.; Asimakopoulos, George; Stavrou, Sofoklis; Daskalakis, George; Koutroumanis, Pelopidas; Sindos, Michael; Theodora, Marianna; Katerelos, Panos; Kostis, Evangelos; Gavrili, Stavroula; Kossyvakis, Athanassios; Theodoridou, Maria; et al.
Abstract: Influenza is associated with an increased risk for serious illness, hospitalization and/or death in pregnant women and young infants. We prospectively studied the effectiveness of a quadrivalent inactivated influenza vaccine (QIV) in pregnant women and their infants during the 2018–2019 influenza season. A QIV was offered to pregnant women cared in a maternity hospital in Athens. Women were contacted weekly by telephone during the influenza season and PCR test was offered to women or infants who developed influenza-like illness (ILI). We studied 423 pregnant women and 446 infants. Unvaccinated pregnant women had a 7.5% probability to develop laboratory-confirmed influenza compared to 2.1% among vaccinated women (Odds ratio: 3.6; confidence intervals: 1.14–11.34, p-value = 0.029). Infants whose mothers were not vaccinated had a 7.9% probability to develop laboratory-confirmed influenza compared to 2.8% among infants of vaccinated mothers (Odds ratio = 2.849, confidence intervals: 0.892–9.102, p-value = 0.053). Cox regression analyses showed that QIV vaccination was significantly associated with a decreased probability for laboratory-confirmed influenza, ILI, healthcare seeking and hospitalization among pregnant women and a decreased probability for laboratory-confirmed influenza, healthcare seeking and prescription of antibiotics among infants. The effectiveness of QIV against laboratory-confirmed influenza was 72% among pregnant women and 64.5% among infants during the 2018–2019 influenza season. Vaccination of pregnant women with the QIV was associated with a lower risk for laboratory-confirmed influenza for them and their infants during the influenza season. Our findings strongly support the World Health Organization recommendations for vaccinating pregnant women against influenza.